2009
DOI: 10.1089/sur.2007.092
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Management, and Prognosis of Secondary Non-Postoperative Peritonitis: A French Prospective Observational Multicenter Study

Abstract: Patients with non-postoperative peritonitis should be considered high risk and should receive appropriate initial therapy. The presence of Enterococcus spp. in peritoneal cultures significantly increased morbidity but not the mortality rate. Appendiceal peritonitis that was less severe and had a better prognosis than peritonitis originating in other sites should be considered a special case in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
2
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 30 publications
6
58
2
9
Order By: Relevance
“…This finding is consistent with multiple studies that have demonstrated an association between inappropriate antibiotic use and increased risk of therapeutic failure and mortality in the context of IAI [19][20][21][22]. This finding emphasizes the need to tailor empiric therapy utilizing patient specific factors in order to optimize outcomes for patients with IAI.…”
Section: Tellor Et Alsupporting
confidence: 90%
“…This finding is consistent with multiple studies that have demonstrated an association between inappropriate antibiotic use and increased risk of therapeutic failure and mortality in the context of IAI [19][20][21][22]. This finding emphasizes the need to tailor empiric therapy utilizing patient specific factors in order to optimize outcomes for patients with IAI.…”
Section: Tellor Et Alsupporting
confidence: 90%
“…Therefore, it seems that enterococci are associated with comorbidity, but we could not demonstrate an association with mortality. In a previous study, the presence of enterococci in peritoneal fluid cultures significantly increased the rate of morbidity but not that of mortality (6), while other authors established an association between polymicrobial infections involving enterococci and increased mortality (3,20,21).…”
Section: Discussionmentioning
confidence: 86%
“…More recent studies excluding postoperative cases have reported on the minor role of enterococci in secondary peritonitis in relatively healthy patients (20), although others report that the presence of this entity in cultures of peritoneal fluid significantly increases the rate of morbidity but not the rate of mortality (6).…”
mentioning
confidence: 99%
“…Electronic operating room log was browsed for all abdominal emergency surgery cases, which were further analysed from electronic patient records, and all consecutive operatively treated adult patients with diffuse secondary peritonitis due to perforation in GI tract between January 1, 2012 and December 31, 2013 were included in the study cohort. Patients with appendicitis or cholecystitis were excluded due to their better prognosis and straightforward treatment protocols [2,13,16]. Further, four patients were excluded from the study group because they were already receiving ICU care due to another disease (two patients with severe pancreatitis, one early postoperative period after lung transplantation and one postoperative period after operation for ruptured abdominal aortic aneurysm) during the time of GI perforation.…”
Section: Methodsmentioning
confidence: 99%
“…There are a number of studies and reviews that have analysed and listed prognostic factors in peritonitis [1,2,4,6,[12][13][14][15]. None of these previous studies specifically concentrate on preoperative variables.…”
Section: Introductionmentioning
confidence: 99%